2021
DOI: 10.3390/v13040654
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myeloid Cells in Oncolytic Reovirus-Based Cancer Therapy

Abstract: Oncolytic reovirus preferentially targets and kills cancer cells via the process of oncolysis, and additionally drives clinically favorable antitumor T cell responses that form protective immunological memory against cancer relapse. This two-prong attack by reovirus on cancers constitutes the foundation of its use as an anticancer oncolytic agent. Unfortunately, the efficacy of these reovirus-driven antitumor effects is influenced by the highly suppressive tumor microenvironment (TME). In particular, the myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“… 40 OV-treatment has been shown to cause the repolarization of immune-suppressive I.T M2 macrophages towards an M1 phenotype that express pro-inflammatory cytokines and chemokines including IFN-γ, CXCL10, IL-6, IL-2, IL-12, IL-21 among others that reinforce the antitumor immune environment. This effect has been noted with several OVs including GLV-1h68 41 (GL-ONC1, Lister strain VV) and Ad5-D24-RGD 42 (tumor-retargeted oncolytic AdV), VSV, 43 HSV, 44 RV, 45 paramyxoviruses 46 (MeV and MuV) and VV-IL21, 34 demonstrating OVT as an effective mechanism by which to control M1/M2 ratios in the TME. A recent report revealed that treatment with an ICP34.5 -deleted HSV vector (HSV1716) was able to not only promote M1 polarization of macrophages, but macrophages could also take up, replicate and release HSV1716 into the TME, providing a viral amplification route and promoting the oncolytic effect of the treatment.…”
Section: The Effect Of Ovt On the Immune Milieu Within Thementioning
confidence: 77%
“… 40 OV-treatment has been shown to cause the repolarization of immune-suppressive I.T M2 macrophages towards an M1 phenotype that express pro-inflammatory cytokines and chemokines including IFN-γ, CXCL10, IL-6, IL-2, IL-12, IL-21 among others that reinforce the antitumor immune environment. This effect has been noted with several OVs including GLV-1h68 41 (GL-ONC1, Lister strain VV) and Ad5-D24-RGD 42 (tumor-retargeted oncolytic AdV), VSV, 43 HSV, 44 RV, 45 paramyxoviruses 46 (MeV and MuV) and VV-IL21, 34 demonstrating OVT as an effective mechanism by which to control M1/M2 ratios in the TME. A recent report revealed that treatment with an ICP34.5 -deleted HSV vector (HSV1716) was able to not only promote M1 polarization of macrophages, but macrophages could also take up, replicate and release HSV1716 into the TME, providing a viral amplification route and promoting the oncolytic effect of the treatment.…”
Section: The Effect Of Ovt On the Immune Milieu Within Thementioning
confidence: 77%
“…The presence of M2 macrophages in the TME is a powerful prognostic factor for low overall survival in most cancers [84]. At the TME level, OVs act on M2 macrophages, which are repolarized to an M1 phenotype, and express various proinflammatory cytokines and chemokines (IFN-γ, CXCL10, various interleukins), among others, that reinforce the antitumor immune environment; this effect has been shown in some studies on OVs, including VSVs, HSVs, reoviruses (RV), paramyxoviruses (MeV and MuV), GLV-1h68 and Ad5 D24-RGD [74,[85][86][87][88][89][90] Involvement of NK cells NK cells are important mediators of oncolytic virotherapy. Also, NK cells are involved in the fight against viral infections, and therefore, they can have a detrimental effect on the efficacy of OVs.…”
Section: Involvement Of Macrophagesmentioning
confidence: 92%
“…pembrolizumab in either recurrent inoperable or progressive head and neck squamous cell carcinoma (HNSCC). 227 NCT04391049 studies the side effects of i.t . telomelysin when given together with i.v .…”
Section: Oncolytic Virotherapymentioning
confidence: 99%